Educational Robotics intervention on Executive Functions in preschool children: A pilot study. (June 2017) - Di Lieto, Maria Chiara; Inguaggiato, Emanuela; Castro, Emanuela; Cecchi, Francesca; Cioni, Giovanni; Dell'Omo, Marta; Laschi, Cecilia; Pecini, Chiara; Santerini, Giacomo; Sgandurra, Giuseppina; Dario, Paolo
Abstract: Educational Robotics (ER) is known for its effects on academic achievement and scientific concepts. Few studies have demonstrated ER effects on cognitive skills and no evidence exists on the role of ER in promoting Executive Functions, key elements in early school readiness and cognitive milestone achievements. The aim of this study was to evaluate, for the first time, the short-term effects in Preschool children of an intensive ER training on Executive Functions. A sample of 12 children (age range: 5–6 years) took part to an intensive ER-Lab for 13 sessions (6 weeks) by using a bee-shaped robot, called Bee-Bot ® . The children were tested three times (baseline, pre and post ER-Lab) with a neuropsychological battery. The main finding was a significant improvement in both visuo-spatial working memory and inhibition skills after the ER-Lab period, with a significant effect also on robot programming skills. These data provide scientific support to the hypothesis that ER is suitable in progressively improving abilities in planning and controlling complex tasks in early childhood, fostering executive functions development. Highlights: Educational Robotics (ER) benefits on Executive Functions in preschool children. Intensive ER training may improve working memory and inhibition skills. This study integrates ER within a theoretical framework of cognitive development.